The hydrogeomorphology of the Featherstone Kloof Catchment - Ntakumba, Stanley Sixolile (Rhodes University, Faculty of Science, Department of Geography)
Wetlands are an important part of the landscape as hydrogeomorphological ecosystems. Over the centuries their importance has not received relevant attention; instead they have been treated as wastelands impeding development for maximum economic benefits. Research evidence from different parts of the world has influenced the change of such negative perceptions to an extent that the issue of wetlands' rehabilitation/restoration, conservation and management is firmly on the global agenda and local agendas of various countries, as evidenced by the adoption of the Ramsar Convention in 1971, and the Working for Water and Working for Wetlands programmes of the South African government. The aim of this research was to investigate the hydrological and geomorphological functions of a headwater wetland located in the Featherstone Kloof Catchment near Grahamstown, South Africa. The research was based on the hypotheses that wetlands store sediments, attenuate floods, store water and prolong downstream flows. A literature survey was conducted to gauge the state of knowledge about wetlands, particularly their hydrogeomorphology. An attempt was made to locate the study area within the broad historical and spatial context using a number of methods, including the radiocarbon dating of wetland sediments, the review of relevant literature and the analysis of historical hydroclimatic data. The results revealed that the wetland has existed for approximately 2000 years - as the oldest radiocarbon date obtained was 1850Â±50 BP. An analysis of more than a century (+120 years) long Grahamstown rainfall series indicated a steady fluctuation of rainfall around the mean, with regular decada1 cycles of wet and dry spells. Years with more rain below average were more common than those with higher rainfall, and storms events were quite common in the III area over the period. The distribution of seasons in the area over a calendar year period was demonstrated through the use of evaporation data. An intensive monitoring of hydrological and geomorphological variables was carried out using a combination of methods. The topography of the instrumented site was determined using a Total Station from reference benchmarks. Hydrological measurements included a nest of forty-eight piezometers for water table monitoring, and streamflow gauges at the upstream and downstream limits of the study site. Soil stratigraphic analysis was carried out through field techniques and laboratory measurements. A survey of wetland sediments was carried out after the main floods events. Data generated were used to analyse relationships between various variables and their role on the functioning of the wetland. The water balance of the wetland was quantified. The results indicated that the wetland was able to perform the cited hydrogeomorphological functions to some extent. For example, one of the key findings of this research is that the wetland was important in sustaining base flows under normal circumstances. However, the wetland did little to attenuate large floods. The results also revealed some important questions that require further research, including the role played by extreme flood events in altering wetland characteristics, the contribution of each water balance component in the hydrological functioning of wetlands, and importance of quantifying sediment budgets of headwater wetlands. The study demonstrated the complex nature of the wetland hydro geomorphology and that certain questions about wetlands require direct field monitoring to be better understood.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Wetlands -- South Africa; Wetland restoration -- South Africa -- Featherstone Kloof Catchment; Wetland conservation -- South Africa -- Featherstone Kloof Catchment; Wetland management -- South Africa -- Featherstone Kloof Catchment; Wetland ecology -- South Africa -- Featherstone Kloof Catchment